2018
DOI: 10.1055/a-0732-5317
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up after endoscopic resection for superficial esophageal squamous cell carcinoma: a multicenter Western study

Abstract: Background Endoscopic mucosal resection (EMR) and endoscopic submucosal dissection (ESD) are the first-line treatments for superficial esophageal squamous cell carcinoma (SCC). This study aimed to compare long-term clinical outcome and oncological clearance between EMR and ESD for the treatment of superficial esophageal SCC. Methods We conducted a retrospective multicenter study in five French tertiary care hospitals. Patients treated by EMR or ESD for histologically proven superficial esophageal SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 35 publications
2
68
0
Order By: Relevance
“…In the current study, the complete lateral resection rate was 66 % for dysplasia and 92 % for invasive carcinoma, comparable to that described in two single-center and one multicenter study on endoscopic resection of early esophageal SCC (lateral margins positive for carcinoma in 8.3 % to 9.5 % of lesions) [21][22][23]. It is interesting to note that local recurrence rate was inferior to complete lateral resection rate for dysplasia which may be due to pathological examination limitations due to cautery artifacts or due to cautery effect on non-resected adjacent mucosa.…”
Section: Totalsupporting
confidence: 88%
“…In the current study, the complete lateral resection rate was 66 % for dysplasia and 92 % for invasive carcinoma, comparable to that described in two single-center and one multicenter study on endoscopic resection of early esophageal SCC (lateral margins positive for carcinoma in 8.3 % to 9.5 % of lesions) [21][22][23]. It is interesting to note that local recurrence rate was inferior to complete lateral resection rate for dysplasia which may be due to pathological examination limitations due to cautery artifacts or due to cautery effect on non-resected adjacent mucosa.…”
Section: Totalsupporting
confidence: 88%
“…11 Furthermore, ESD was associated with a higher recurrence-free survival in infiltrative tumors. 20 Second, all ESDs were conducted under general anesthesia and performed by only one of three doctors who had 10 years' experience in endoscopic operation, and who collectively have performed an average of 30 ESDs. Recently Song et al 21 reported that conscious sedation was an independent risk factor for incomplete resection, while general anesthesia improves the outcomes of esophageal ESD.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed complications in our study were mainly postoperative strictures (11.5%), and this rate is similar to those described in recent studies. 20 Treatment of benign esophageal strictures with serial endoscopic dilatation using bougies or balloons has been established as a standard therapy, and it is associated with an immediate 80-90% success rate in relieving dysphagia. 31,32 Furthermore, temporary stent placement was a late step in the treatment strategy of benign esophageal strictures.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 A multicenter Western study showed that, in such patients, the risk of metastatic recurrence strongly decreased in those with adjuvant CRT (40-50 Gy) as compared to those without additional treatment (0.0 vs 34.6%). 34 However, in clinical practice, less than half of eligible elderly patients underwent additional treatment and, furthermore, esophagectomy, which is the standard treatment method for SESCC, 28,29 is rarely selected as an additional treatment approach after ER. 78 Esophagectomy is a highly extensive procedure 79 and is associated with both increased mortality (3.63-3.72%) 80 and a drastic deterioration of health-related QOL.…”
Section: Advantages and Disadvantages Of Additional Treatmentmentioning
confidence: 99%
“…However, some patients do not undergo additional treatment because of concerns regarding the risk of the treatment, such as old age and/or severe comorbidities. [30][31][32][33][34][35] With the ongoing growth of the aged population, the rate of elderly patients among the total population with upper GI neoplasia in Japan has also been rising. 36,37 Elderly patients have unique age-related variations in their physical condition that contribute to increased complexity in treatment decision-making.…”
Section: Introductionmentioning
confidence: 99%